Formation of microbiology as a scientific discipline (to the 100th anniversary of the death of I. I. Mechnikov) - Ruda, S. P. (History of science and technology, 2017)
The article is devoted to the role of I. I. Mechnikov in the origin and development of microbiological science. There is shown the importance of international scientific schools of the late XIX – early XX centuries in realization of this process.